Physical and cognitive characteristics of a group exercise program for children treated for brain tumors - Ryan, Jennifer L.; Johnston, Krista; Bouffet, Éric; Bartels, Ute; Timmons, Brian W.; de Medeiros, Cynthia B.; Mabbott, Donald J. (Frontiers in Rehabilitation Sciences, 2026)
BackgroundChildren treated for brain tumor (CTBT) experience lasting physical and cognitive impairments that impact quality of life. Given the pervasive impact of brain tumor treatments on cognition, we designed a group exercise program with the specific goal of improving cognition in CTBT. A feasibility study evaluating the program demonstrated improved cognitive and physical outcomes. However, the exercises varied across sessions to maximize participant engagement throughout the 12-week program, which made it difficult to describe the program contents and identify how each element contributed to the observed improvements.ObjectiveAs a precursor to identifying the effective elements within the group exercise program for CTBT, this study characterized the content of our program according to the exercise categories observed in the exercise sessions, the physical fitness components within the exercises, and the cognitive demand of the exercises.MethodsThis retrospective descriptive analysis coded the content of 50 videos from the exercise program sessions by exercise category (warm-up, aerobic training, games, sports, cool-down), physical fitness components (cardiovascular, coordination, speed, agility, object control, strength, balance, flexibility), and cognitive demand (low, medium, high). Data were descriptively summarized.ResultsMost of the exercise session was spent on games, followed closely by sports. 33% of the exercise session involved exercises with high amounts of cardiovascular content and 46% of the exercise session involved exercises with moderate amounts of cardiovascular content. Exercises with high cognitive demand had the most coordination and object control content. Exercises with medium cognitive demand had the most cardiovascular content.ConclusionThe presence of exercises with either high cardiovascular content or high coordination was the hallmark of our group exercise program for CTBT. These features should be manipulated in future exercise program evaluations to determine their impact on cognitive and physical outcomes in CTBT.